2011
DOI: 10.1007/s00018-011-0889-x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the role of hCG: new regulation of the angiogenic factor EG-VEGF and its receptors

Abstract: Endocrine gland-derived vascular endothelial growth factor (EG-VEGF) is an angiogenic factor reported to be specific for endocrine tissues, including the placenta. Its biological activity is mediated via two G protein-coupled receptors, prokineticin receptor 1 (PROKR1) and prokineticin receptor 2 (PROKR2). We have recently shown that (i) EG-VEGF expression peaks between the 8th and 11th weeks of gestation, (ii) its mRNA and protein levels are up-regulated by hypoxia, (iii) EG-VEGF is a negative regulator of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 52 publications
(90 reference statements)
1
64
0
3
Order By: Relevance
“…5,29 Altogether our findings have demonstrated that EG-VEGF induces a PIH phenotype if maintained beyond the first trimester of pregnancy and provides evidence to suggest that maintenance of elevated EG-VEGF during the second and third trimesters of pregnancy contributes to the attenuation of this pathogenesis. These in vivo observations are consistent with our previous studies using human tissues during normal pregnancy 11,16,31,32 and also in pathological pregnancies. 9,12,13 Therefore, this study provides novel insights into the fine role of EG-VEGF in the development of PIH and the attenuation of its pathological symptoms, once the pathology is established.…”
Section: Discussionsupporting
confidence: 93%
“…5,29 Altogether our findings have demonstrated that EG-VEGF induces a PIH phenotype if maintained beyond the first trimester of pregnancy and provides evidence to suggest that maintenance of elevated EG-VEGF during the second and third trimesters of pregnancy contributes to the attenuation of this pathogenesis. These in vivo observations are consistent with our previous studies using human tissues during normal pregnancy 11,16,31,32 and also in pathological pregnancies. 9,12,13 Therefore, this study provides novel insights into the fine role of EG-VEGF in the development of PIH and the attenuation of its pathological symptoms, once the pathology is established.…”
Section: Discussionsupporting
confidence: 93%
“…Expression of the immunoinhibitor CD274 was shown to be low in early first trimester and to increase around the onset of the second trimester (18). A different regulation in trophoblastic endocrine gland-derived (EG) vascular endothelial growth factor (VEGF) secretion by hCG via EG-VEGF receptors was also reported between early and late first-trimester placentas (6).…”
Section: Discussionmentioning
confidence: 96%
“…The effect of hCG on EG-VEGF expression is transcriptional and is mediated by a cAMP response element (CRE2) located at -383 bp within the EG-VEGF promoter region. [23]. Importantly, hCG regulation of EG-VEGF expression has also been reported in the ovary [3].…”
Section: Opinionmentioning
confidence: 92%